The economic side of an oral sugar lowering therapy intensification by glucagon-like peptidt-1 receptor agonists - S. K. Zyryanov; I. N. Dyakov (Izdatelstvo OKI, 2022)
The effective control of Diabetes Mellitus (DM) is an actual problem from optimal expenditures of health care system point of view. Glucagon-like peptide-1 receptor agonists (GLP-1 RA) are one of the modern options for glycemia control in DM Type 2 and included in all current guidelines for the treatment control. The economic comparative aspects of the use of these drugs in the local conditions are important for decision making. Materials and methods. The comparative economic evaluation for injectable remedies such kind as fixed combination of insulin glargine + lixisenatide (iGlaLixi), exenatide (Exe), dulaglutide (Dula), liraglutide (Lira), semaglutide (Sema) and fixed combination of insulin degludec + liraglutide (iDegLira) has been performed base on published clinical data of efficacy in patients who did not reach target of HbA1c on oral antidiabetic drugs treatment. Number of patients with HbA1c <7 % was chosen as efficacy criterion. Non-direct comparison with Odds Ratio (OR) calculation was prepared. Direct and indirect costs (medications, treatment of CV-complications, GDP loses etc.) were indicated and calculated based on constructed model. Sensitivity analysis has been provided for validation of results. Results. Pharmacoeconomic analysis for all drugs included into analysis has shown of economic advantages of effective DM2T control. iGlaLixi has demonstrated economic advantages as well usage aGLP-1 only (direct costs decreasing vs Exe on 37,8 %, vs Dula on 31,8 %, vs Lira on 63,5 %, vs Sema - on 41,9 %) as vs iDegLira - on 36,1 %. iGlaLixi decreased a total cost (direct and non-direct) better than Exe, Dula, Lira and Sema (on 30,7; 22,3; 52,1 and 30,4 % accordingly. Conclusion. An effective control of DM2T with GLP-1 RA and medicines on their based has an economic value because lead to expenditures for complications decreasing from government position.